PEMANFAATAN WEBSITE ABSENSI BERBASIS GEOLOCATION DAN FACE VERIFICATION UNTUK KARYAWAN LAPANGAN PADA PERUSAHAAN KONSTRUKSI JALAN - Nyoman Krisna Ari Sudarsana; I Made Widiartha; I Dewa Made Bayu Atmaja Darmawan (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
A web-based attendance system utilizing geolocation and face verification was developed to improve the efficiency of attendance management for field employees in a road construction company. The system enables employees to check in independently from project locations using a 2 km geofencing radius and facial verification through selfie capture. This replaces conventional fingerprint attendance that requires physical presence at the head office. The system also includes an admin dashboard for monitoring attendance history based on selected date ranges. Training and socialization activities were conducted to ensure user understanding and adoption of the system. The evaluation results show that users can accept and feel quite satisfied with this attendance system. This demonstrates that the application of information technology can contribute significantly to workforce management in the construction sector.